Visual communications of tomorrow natural, efficient, and flexible. - Konrad, J. (IEEE Communications magazine)
In the last decade, we have witnessed a phenomenal growth of communication and information technologies. These technologies have greatly simplified and even enriched our daily lives; cellular telephony and the Internet are probably the most striking examples. A particularly promising, and at the same time challenging, aspect of both technologies is the transmission and use of visual information. The author overviews the state of visual communication at the end of the 20th century, discusses today's challenges, and outlines some future directions